Assessment of the Pollution Status of Eleyele Lake, Ibadan, Oyo State, Nigeria - Olayinka, Oluwafunmilayo O. (J Health Pollut, 2017)
BACKGROUND. Lakes are a vital water resource, but are adversely affected by pollutants such as heavy metals and polychlorinated biphenyls (PCBs) from urban, agricultural and industrial activities. This can give rise to potential pollution-related health problems such as cancer and infectious diseases. Risk assessments are necessary to determine the degree of pollution and its effects on human health and ecological systems. OBJECTIVES. This study assessed the pollution status and a risk assessment was calculated to determine the degree of the pollution and its effects on the human health and the ecological system of Eleyele Lake in Ibadan, Nigeria. METHODS. Physical and chemical parameters, heavy metals and PCBs were determined in the lake water using standard methods from December 2013 to February 2014 at ten different sites of anthropogenic activity. RESULTS. Water pH ranged from 6.00–7.50, while electrical conductivity ranged from 205.00–221.00 μs/cm(3). Dissolved oxygen ranged from 0.30–6.00 mg/L and total dissolved solids ranged from 105.00–113.00 mg/L. Phosphate levels ranged from 13–0.99 mg/L. Nitrate and sulphate in the dry season ranged from (3.10–3.80 and 35.81–40.97 mg/L) and (0.12–0.37 and 6.10–10.30 mg/L) in the wet season. Heavy metal concentrations were in the order cadmium (Cd) > zinc (Zn) > copper (Cu) > chromium (Cr) > lead (Pb) for the dry season and Cd > Zn > Cr > Pb > Cu for the wet season. Total PCBs ranged from 493.90–732.55 μg/L and 52.00–390.03 μg/L for the dry and wet seasons, respectively. All determined physical and chemical parameters were within permissible levels, while heavy metals and PCB concentrations were higher than permissible levels. DISCUSSION. The hazard quotients and carcinogenic risk values were greater than acceptable limits, indicating that PCBs in Eleyele lake water pose adverse health effects to the local population. It was observed in this study that lower chlorinated PCBs were more prevalent than higher chlorinated PCBs. This may be attributed to the fact that the lower chlorinated PCBs are influenced by atmospheric deposition as a result of their volatility, and they are more susceptible to atmospheric transport than highly chlorinated PCBs. CONCLUSIONS. PCBs possess serious health risks to the population that depends on the lake as a source of domestic water and its aquatic organisms. Efforts are needed to reduce anthropogenic influence on the lake through strict environmental controls.